2022
DOI: 10.3390/su14095735
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability and Risk Management—The U-Shaped Relationships of Disaggregated ESG Rating Scores and Risk in the German Capital Market

Abstract: This study addresses the relationship between the (dis)aggregated ESG rating and different types of risk (i.e., market risk, idiosyncratic risk, total risk) in the German stock market. We investigate not only the overall ESG rating and the E, S, and G pillar scores but also all the underlying category scores. Thereby, we provide in-depth insight into diverse CS operations. We cover 454 firm years (2012–2019) using ordinary least squares regression with firm and year fixed effects. Our main insights are the U-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
1
10
0
3
Order By: Relevance
“…Accordingly, investors show more interest in investing in these socially responsible institutes. This result of the negative effect of the S score on volatility is consistent with Eratalay and Ángel (2022), Engelhardt et al (2021), and Korinth and Lueg's (2022) findings that proved the significant effect of the S score on volatility. Buallay (2018) demonstrated an adverse impact on the performance of Islamic banks.…”
Section: Results Of Regression Analysis Of Volatilitysupporting
confidence: 90%
See 2 more Smart Citations
“…Accordingly, investors show more interest in investing in these socially responsible institutes. This result of the negative effect of the S score on volatility is consistent with Eratalay and Ángel (2022), Engelhardt et al (2021), and Korinth and Lueg's (2022) findings that proved the significant effect of the S score on volatility. Buallay (2018) demonstrated an adverse impact on the performance of Islamic banks.…”
Section: Results Of Regression Analysis Of Volatilitysupporting
confidence: 90%
“…The same outcomes were proved by Engelhardt et al (2021), who found that European firms with solid ESG scores were accompanied by greater abnormal returns and less stock volatility. In addition, Korinth and Lueg's (2022) findings suggested that the level of sustainability was the main factor determining the strength of ESG's impact on the risk. Ilhan et al (2019) applied a comparison study between conventional and ESG portfolios; the results found that firms with low ESG profiles reflected in high carbon emissions faced more risk.…”
Section: Esg Scores and Return Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The second research trend examines the topic concerning corporate sustainability and risk management [20][21][22][23]. For example, reference [21] is essential for understanding the drivers of corporate sustainability within South African organizations and how they intersect with risk management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second research trend examines the topic concerning corporate sustainability and risk management [20][21][22][23]. For example, reference [21] is essential for understanding the drivers of corporate sustainability within South African organizations and how they intersect with risk management. It highlights the link between sustainability and long-term organizational performance, indicating that sustainability and risk management should not be treated as separate entities.…”
Section: Literature Reviewmentioning
confidence: 99%